2015
DOI: 10.1075/dujal.4.2.07oom
|View full text |Cite
|
Sign up to set email alerts
|

The EPPM put to the test

Abstract: Fear appeals are frequently used in health communication, for example in anti-smoking campaigns. Of the different theoretical models that predict and explain how fear appeals work, the Extended Parallel Process Model (EPPM; Witte, 1992) is probably used most often. However, most propositions of the EPPM were not explicitly tested, or received mixed empirical support (Popova, 2012). To clarify the relationships between the variables of the EPPM, four of the EPPM's propositions were tested by performing correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Studies have shown that self-efficacy, regardless of high perceived severity, can have a significant predictive role in health and self-care behavior ( 24 ). Although other research findings showed that response efficacy ( 25 ) and perceived susceptibility ( 26 ) have more predictive power in self-care behavior, in another study results showed self-efficacy as the most important factor in postnatal self-care behavior (physical activity and eating habits) in diabetic women ( 27 ). A study showed self-efficacy as an important factor in participation of women in the use of condoms ( 28 ).…”
Section: Discussionmentioning
confidence: 84%
“…Studies have shown that self-efficacy, regardless of high perceived severity, can have a significant predictive role in health and self-care behavior ( 24 ). Although other research findings showed that response efficacy ( 25 ) and perceived susceptibility ( 26 ) have more predictive power in self-care behavior, in another study results showed self-efficacy as the most important factor in postnatal self-care behavior (physical activity and eating habits) in diabetic women ( 27 ). A study showed self-efficacy as an important factor in participation of women in the use of condoms ( 28 ).…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, when in fear control (maladaptive response), people engage in defensive mechanisms aimed at reducing fear, such as denial (Ooms et al, 2016;Witte, 1994). Thus: H3: Participants exhibiting a maladaptive response will report greater levels of denial compared to participants exhibiting an adaptive response.…”
Section: Introductionmentioning
confidence: 99%
“…First, those with high perceived efficacy will engage in danger control (i.e., adaptive response) which leads to positive changes in attitude, intention, and behavior. Second, those with low perceived efficacy will engage in fear control (i.e., maladaptive response), including defensive avoidance, reactance, and denial (downplaying the message or stating that the message is trying to manipulate them) (Ooms, Jansen, & Hoeks, 2016;Witte, 1992Witte, , 1994. In the case of tobacco use, fear appeals could lead to adaptive responses such as increased intention to quit, quit attempts, and intention to not use tobacco, or maladaptive responses such as denial of the threat and reactance (Cho et al, 2016;Popova, 2014;Thrasher et al, 2016;Wong & Cappella, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A number of gaps have been identified within the literature on the EPPM: none of the core theoretical propositions of the EPPM have received complete support, there are inconsistencies between the level of examination given to each proposition, there is a lack of operational definitions for the 'critical point' and what constitutes a 'true control', and a lack of in-depth experimental assessments of the model processes (Maloney et al, 2011;Ooms et al, 2015;Popova, 2012). When assessing illnesses and their related health behaviours, further complications can arise as inconsistent results could be attributed to potential differences in the specific illnesses and health behaviours (Rimal, 2001).…”
Section: 2mentioning
confidence: 99%